Medical biochemistry - Baynes, John W; Dominiczak, Marek H (Mosby, 1999)
Univ. of South Carolina, Columbia. Textbook for understanding biochemistry as an everyday science. For medical students. Each chapter includes \'Advanced Concepts\' which point to new developments or more specialized topics. All topics are presented in a clinical context and illustrated with clinical examples. Very colorful format. Softcover.
Keywords: biochemie; Biochemistry